The Effectiveness of Blood Clam Shell (Anadara granosa) as an Adsorbent to Improve Peat Water Quality - Aqifa Arifah (FMIPA, Universitas Tanjungpura, 2023)
Research has been carried out to determine the effectiveness of blood clam (Anadara granosa) shell adsorbents in improving the quality of peat water. Blood clam shells were mashed with variations in particle size of 8 mesh, 50 mesh and 150 mesh, then an adsorption process was carried out with a mass ratio of adsorbent and peat water of 1:10. The physical and chemical parameters tested in this study included turbidity, color, Total Dissolved Solid (TDS), and pH. Based on the test results with a contact time of 12 hours, peat water levels increased for all parameters along with increasing particle size. Meanwhile, within 7 days of contact time, the results of the peat water test experienced a decrease in levels for all parameters along with increasing particle size and was a good optimum contact time in the adsorption process. The results obtained show that for the parameters of turbidity, Total Dissolvesd Solid (TDS), and pH have met the standard set by the Minister of Health of the Republic of Indonesia No. 32 of 2017, only the color parameter does not meet the standard in improving the quality of peat water.